Immediate response to prasugrel loading in patients with ST-elevation myocardial infarction: Predictors and outcome. Issue 144 (August 2016) - Koifman, Edward; Beigel, Roy; Herscovici, Romana; Fefer, Paul; Rozenberg, Nurit; Sabbag, Avi; Biton, Yitschak; Segev, Amit; Shechter, Michael; Asher, Elad; Matetzky, Shlomi
Abstract: Introduction: Information regarding immediate response to novel P2Y12 inhibitors in ST-elevation myocardial infarction (STEMI) is scarce and has been associated with adequate reperfusion. Recent studies have shown that the onset of anti-platelet effects of novel P2Y12 inhibitors in patients with STEMI might be slower and more variable than in stable coronary syndrome. We aimed to assess the predictors and significance of immediate platelet response to prasugrel loading in STEMI. Methods: Platelet aggregation (PA) was prospectively evaluated in STEMI patients upon prasugrel loading and at primary percutaneous coronary intervention (PPCI). Early platelet responsiveness was defined as percent reduction of PA from baseline to PPCI, divided by the time lapse from loading to PPCI. High- and low-platelet responsiveness was defined as above and below the median value respectively. Results: Fifty consecutive STEMI patients (age 58 ± 8, 90% male) underwent PPCI with a mean door-to-balloon time of 42 ± 15 min. Mean PA upon prasugrel loading and at PPCI was 76 ± 9% and 63 ± 19%, respectively. Older age and prior aspirin use were predictors of low platelet responsiveness to prasugrel [β = (− 0.33), p = 0.02 and β = (− 0.28), p = 0.04, respectively]. Fast compared with slow responders demonstrated more frequent early ST resolution (93% vs. 72%, p = 0.02) and lower peak troponin levels (76 ± 62 μg/L vs. 48 ± 28 μg/L, p = 0.05). Conclusions: Immediate platelet responsiveness to prasugrel among STEMI patients is highly variable and inversely associated with older age and prior aspirin use. Fast compared with slow responders have improved reperfusion and infarct size markers. Highlights: Early response to thienopyridine was linked to improved outcome in STEMI patients. Age and prior aspirin therapy were inversely related to early response to prasugrel. Early response is linked to ST segment resolution and peak troponin levels.